A facilitating effect of prosodic transfer on non-native fluent speech listening. Issue 6 (2nd July 2016) - Morrill, Tuuli H.
ABSTRACT: Native speakers of a language use metrical structure, phonotactics, and phonetic cues in word segmentation; however, this knowledge can interfere with non-native speech perception and second language learning. Prosodic transfer effects are typically investigated with isolated words and phrases, or simple artificial languages; the current study examines how prosody affects perception and word learning in acoustically complex natural speech. Two experiments test effects of native language prosody on word identification in prosodically similar and dissimilar languages; they also test the types of language exposure and learning tasks in which prosodic transfer may occur. English speakers were exposed to one of two non-native languages (Finnish or Japanese) in three training conditions. Results indicate that learning can occur thru exposure to fluent speech in a prosodically similar language and suggest that effects of prosody on fluent speech perception are an important factor in early stages of second language acquisition.